The FLUKA Monte Carlo code coupled with the local effect model for biological calculations in carbon ion therapy - Mairani, Andrea; Brons, Stephan; Cerutti, F.; Fassò, A.; Ferrari, A.; Krämer, M.; Parodi, Katia; Scholz, M.; Sommerer, Florian (Physics in medicine and biology, 2010)
Clinical Monte Carlo (MC) calculations for carbon ion therapy have to provide absorbed and RBE-weighted dose. The latter is defined as the product of the dose and the relative biological effectiveness (RBE). At the GSI Helmholtzzentrum für Schwerionenforschung as well as at the Heidelberg Ion Therapy Center (HIT), the RBE values are calculated according to the local effect model (LEM). In this paper, we describe the approach followed for coupling the FLUKA MC code with the LEM and its application to dose and RBE-weighted dose calculations for a superimposition of two opposed 12C ion fields as applied in therapeutic irradiations.